PENGARUH KUALITAS PELAYANAN PRODI EKONOMI SYARIAH DALAM PENYELESAIAN ADMINISTRASI TERHADAP KEPUASAN MAHASISWA DAN DAMPAKNYA TERHADAP CITRA PRODI EKONOMI SYARIAH - Rudi Aryanto (I-Finance Journal, 2017)
This study aims to find out the quality of Islamic Economy Study Service in completing the administration of student satisfaction and its impact on the image of Islamic Economics Program. The analysis technique used is through t test and R² test. Then in this study there are variables between, then automatically direct and indirect influence must be done so that used path analysis. The results showed that simultaneously tangible, reliability, responsiveness, assurance and emphaty variables significantly influence students' satisfaction in administrative settlement in sharia economic process. Then partially only the responsiveness and empathy variable that has no significant effect on student satisfaction. Student satisfaction variable has a significant influence on image of Islamic Economics Study Program. The tangible variables affect the image of the Islamic Economy Study Program through the students' satisfaction of 60.2%. The variable of reliability affects the image of Islamic Economics Program through student satisfaction of 0.7%. Responsiveness variable affects the image of Islamic Economics Program through student satisfaction of 18%. Assurance variables affect the image of Islamic Economics Program through student satisfaction of 6.7%. Emphaty variables affect the image of Islamic Economic Prodi through student satisfaction of 28.8%.